Research on the Influence of AI and VR Technology for Students’ Concentration and Creativity - Rong, Qiming; Lian, Qiu; Tang, Tianran (Frontiers in Psychology, 2022)
The application of digital technology in teaching has triggered the evolution of traditional teaching. Students have different corresponding relationships under digital behavior. The interactive technology of artificial intelligence (AI) and virtual reality (VR) provides a new driving force for the development of art education and psychology. Firstly, this thesis analyzes the limitations and existing problems of traditional art education, Especially the influence of the teaching mode of art education on the teaching of other disciplines, develop a targeted student-centered digital education program. Secondly, the author used VR equipment and technology to let students experience the virtual world freely, and then the relevant data model was established on the basis of analyzing the reasons affecting students’ creativity and concentration. Thirdly, the data model was applied to art education in order to improve students’ concentration and creativity. Then, the author compared and analyzed the data of the students under different teaching models through questionnaires. The results show that introducing VR and AI technology into art education and encouraging students to carry out deep learning can significantly improve students concentration and creativity. Finally, the influence reasons are analyzed from the perspective of psychology. VR interaction and Artificial Intelligence can be introduced into middle school fine art education which is to the benefit of students’ deep learning, thus students’ concentration and creativity can be improved.